Pengembangan Media Pembelajaran Interaktif Berbasis Smart Apps Creator untuk Meningkatkan Hasil Belajar IPA Siswa Sekolah Dasar - Rukoyah, Siti; Bektiningsih, Kurniana (Postgraduate, University of Mataram, 2024)
This study aims to develop and test the feasibility and effectiveness of interactive media based on Smart Apps Creator to improve student learning outcomes in the subject of Integrated Natural and Social Sciences (IPAS) on energy transformation material. The study involves research and development (R&D) using the ADDIE model. Expert validation for the content and media was 92.8 and 93%, which falls into the very feasible/valid category. The average improvement in student learning outcomes before and after using the Smart Apps Creator-based learning media, measured using the N-gain test, was 0.667, which falls into the moderate category. Teacher and student responses were 100 and 96.4%, respectively, falling into the very practical category. Therefore, the Smart Apps Creator-based learning media is feasible, effective, and practical for teaching to improve student learning outcomes in the subject of IPAS on energy transformation material.